Improved Specific Capacity of Nb2O5 by Coating on Carbon Materials for Lithium‐Ion Batteries. Issue 22 (21st September 2018) - Yang, Fan; Li, Weiyang; Rui, Yichuan; Tang, Bohejin
Abstract: Materials for lithium‐ion batteries (LIBs) with excellent electrochemical performance are of significance to meet the increasing demand for rechargeable batteries. Niobium pentoxide (Nb2 O5 ), as an intercalation material with promising electrochemical properties has caught our attention. In this study, Nb2 O5 nanoparticles were successfully synthesized through a classical sol‐gel process. The nanoparticles with a size of less than 5 nm were uniformly coated on carbon materials, i. e., reduced graphene oxide (rGO) and three‐dimensionally ordered macroporous (3DOM) carbon, under the same proportion, to explore which kind of carbon materials is more suitable to improve the electrochemical performance of Nb2 O5 as an anode for LIBs. Nb2 O5 /3DOM carbon composite exhibited a superior electrochemical performance to the other two materials, where a high reversible capacity of 519 mA h g −1 could be maintained at the current density of 5.0C (C=201.7 mA g −1 ). Furthermore, the specific capacity of Nb2 O5 /3DOM carbon composite maintained 1163 mA h g −1 at the current density of 0.2C (C=201.7 mA g −1 ) after 100 cycles. Abstract : Nb2 O5 nanoparticles and two different Nb2 O5 /carbon composites are synthesized by a sol‐gel process and tested as negative electrodes for lithium‐ion batteries. The Nb2 O5 /3DOM carbon composite exhibited superior electrochemical performance (compared to pure Nb2 O5 and the Nb2 O5 /rGO composite). Thus, 3DOM carbon is more suitable to be a matrix to coat Nb2 O5 as an anode for lithium‐ion batteries than rGO.